The influence of Xhosa traditional music and culture on modern South African jazz : exploring the narratives of six South African jazz musicians - Sepuru, Phuti (University of Pretoria, 2024)
Mini Dissertation (MMus (Performing Art))--University of Pretoria, 2023.